Impact of Shield Under-Passing on Existing Tunnel Settlement Considering Construction Factors - XUE Ziqian; XIA Hongchun; ZHU Xunguo; YAN Huajun (Chengshi guidao jiaotong yanjiu)
[Objective] The construction of a new shield-tunneling tunnel under-passing the existing tunnel can induce the latter′s settlement and deformation. Therefore, it is necessary to study the impact of construction factors on the settlement of the existing tunnel during the shield under-passing process. [Method] Taking the project of Guangzhou Metro Line 22 under-passing Line 3 as an example, multiple groups of numerical model are established based on Midas/GTS NX software. The influence rules of double-line shield tunneling under-passing on the existing tunnel settlement under the influence of two construction factors，soil chamber pressure and grouting pressure，are analyzed. Curve fitting is carried out according to the maximum settlement values of the tunnel corresponding to different soil chamber pressures and grouting pressures. Based on the settlement correction formula of the existing tunnel considering the influence of tunnel burial depth, a prediction formula for the settlement of the existing tunnel caused by double-line shield tunneling under-passing is proposed, which is applicable to Guangzhou area and considering construction factors. [Result & Conclusion] Within a reasonable range, the settlement value of the existing tunnel is negatively correlated with the soil chamber pressure and the grouting pressure. The settlement fitting curve functions of different soil chamber pressures and grouting pressures are capable to predict the settlement of the existing tunnel under the change of multiple construction factor levels. The lower limit of the soil chamber pressure in the under-passing section is 0.236 MPa, and that of the grouting pressure is 0.267 MPa. During the shield tunneling closely under-passing, construction supervision and protection should be strengthened. Appropriate grouting pressure and soil chamber pressure can reduce the disturbance impact on the existing tunnel.